An Integrated Development Model of Cultural and Creative Industry and Rural Tourism Industry Based on Data Mining. (25th April 2022) - Chang, Weifeng
Abstract : In the later stage of industrialization or postindustrialization era, the driving force of human social and economic development mainly comes from technological innovation, cultural creativity, and the development of creative industries, high-tech industries, and service industries. The cultural and creative industries meet the needs of the postindustrial era and the era of knowledge economy. This shows the importance of culture, knowledge, and technology in the rapid economic development. This paper introduces data mining technology and obtains a data mining method system suitable for this study. It mines and analyzes data related to cultural and creative industries and rural tourism industries. It finally obtained that the degree of integration of the two industries in the past six years was 0.498, 0.496, 0.487, 0.498, 0.499, and 0.5, respectively.